2016
DOI: 10.1016/j.biocontrol.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic resistance in Chinese cabbage against black rot by plant growth-promoting rhizobacteria

Abstract: Black rot, caused by Xanthomonas campestris pv. campestris, is the most important and potentially destructive disease of cabbage. The objectives of this study were to select plant growth-promoting rhizobacteria (PGPR) strains and to form strain mixtures with the capacity to elicit induced systemic resistance or to increase plant growth in Chinese cabbage. In preliminary screening, 10 of 12 tested individual PGPR strains (AP136, AP188, AP209, AP213, AP217, AP218, AP219, AP282, AP295, and AP305) reduced the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…velezensis ) increased shoot and root dry weights in the greenhouse test. They found that those individual strains and mixtures increased marketable yield of Chinese cabbage in the field [31]. Our study is in an agreement with previous research that individual or mixtures of PGPR strains can promote plant growth under greenhouse or field conditions and that some PGPR strains can reduce plant-parasitic nematode population density.…”
Section: Discussionsupporting
confidence: 92%
“…velezensis ) increased shoot and root dry weights in the greenhouse test. They found that those individual strains and mixtures increased marketable yield of Chinese cabbage in the field [31]. Our study is in an agreement with previous research that individual or mixtures of PGPR strains can promote plant growth under greenhouse or field conditions and that some PGPR strains can reduce plant-parasitic nematode population density.…”
Section: Discussionsupporting
confidence: 92%
“…Several beneficial bacterial strains isolated from the rhizosphere of Brassica species [16] are associated with plant growth and promoting rhizobacteria (PGPR), such as Agrobacterium , Azospirillum , Bacillus , Enterobacter , Pseudomonas and Rhizobium [17]. These microorganisms can promote plant growth by regulating nutritional and hormonal balances, producing plant growth regulators [18], solubilizing nutrients and inducing resistance against plant pathogens [19]. Some studies have shown that the incorporation of Brassica crops into soil inhibited the growth of a variety of soil-borne pathogens of potato, including Rhizoctonia solani , Phytophthora erythroseptica , Pythium ultimum , Sclerotinia sclerotiorum and Fusarium sambucinum , and reduced subsequent potato seedling disease by 40–83% [20].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Bacillus isolates (MAD-05, Bacillus subtilis and TAD-05, Bacillus licheniformis) showed high antifungal activity of 62.75% and 43.53% PGI, which may contribute to the competition for space and nutrients and secretion of antifungal compounds (Yang et al, 2015). Similarly, Bacillus species have been widely reported to have antifungal activity against a wide variety of phytopathogens (Ji et al, 2014;Kumar et al, 2012;Liu et al, 2016). Therefore, further application of Bacillus isolates as biocontrol agents could be expected.…”
Section: Isolation and Characterization Of Bacteria For Plant Growth mentioning
confidence: 85%